2015
DOI: 10.1007/s00431-015-2531-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of use of complementary and alternative medicine in children with autism spectrum disorder in Europe

Abstract: This study examined the prevalence and correlates of use of complementary and alternative medicine (CAM) among a sample of children with autism spectrum disorder (ASD) < 7 years in 18 European countries (N = 1,680). Forty-seven percent of parents reported having tried any CAM approach in the past 6 months. Diets and supplements were used by 25 % of the sample and mind–body practices by 24 %; other unconventional approaches were used by 25 % of the families, and a minority of parents reported having tried any i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
63
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 36 publications
5
63
2
1
Order By: Relevance
“…Our study’s finding that parents’ use of CHA is more likely for children with ASD who also use medication is consistent with some past research (Owen-Smith et al, 2015; Salomone et al, 2015) and lends some support for our hypothesis that higher services use is correlated with use of CHA. Earlier investigations have, indeed, suggested certain prescription medications (e.g., risperidone) may be efficacious for treating core and associated ASD symptoms (Huffman et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our study’s finding that parents’ use of CHA is more likely for children with ASD who also use medication is consistent with some past research (Owen-Smith et al, 2015; Salomone et al, 2015) and lends some support for our hypothesis that higher services use is correlated with use of CHA. Earlier investigations have, indeed, suggested certain prescription medications (e.g., risperidone) may be efficacious for treating core and associated ASD symptoms (Huffman et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…Past research shows parents of children with greater ASD severity or medical complexity (e.g., comorbid gastrointestinal problems, hyperactivity) (Hall & Riccio, 2012; Perrin et al, 2012; Salomone et al, 2015; Valicenti-McDermott et al, 2013) are more likely to use CHA for their child. We accordingly hypothesized that parent-reported ASD severity (i.e., mild vs. moderate or severe) would be associated with use of CHA; however, our study’s results did not show a statistically significant association of parent-reported ASD severity with CHA use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations